RESPON PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max L.) AKIBAT PEMBERIAN LIMBAH PADAT (SLUDGE) KELAPA SAWIT DAN PUPUK CAIR ORGANIK - Efrida Lubis; Wan Arfiani Barus (AGRIUM: Jurnal Ilmu Pertanian, 2013)
The objective of research was to determinate of growth and production of Soja max (Glycine max L.) with provision sludge oil palm andorganic liquid manure. This research was conducted using Randomized Design Group (RAK) factorial with two factors, namely : sludge (S) which consist of three extent that to S0 = Without Giving, S1 = 2,5 kg/plot, and S2 = 5 kg/plot. While organic liquid manure  Biogrow complete (B) which  consist of three standart are, B0 = Without Giving, B1 = 5 cc/l water, and B2 = 10 cc/l water.Key words : Production, soja max, Sludge, organic liquid manure